Corrosion Inhibition of Mild Steel by Ecofriendly Extract of Croton sparciflorus - KASTHURI*, P.K.; ARULANANTHAM†, A. (Asian Journal of Chemistry, 2009)
The acid extract of Croton sparciflorus containing bio active ingredientshave been used as corrosion inhibitor for mild steel in 1 M HCl.The inhibitor efficiency calculated using weight loss, potentio-dynamicpolarization and impedance methods has been found to be effectiveinhibitor. The effect of temperature on the corrosion behaviour of mildsteel indicated that inhibition increased with increasing temperature. Itfollows Temkin adsorption isotherm. Polarization and impedance studiesrevealed that the inhibitor was mixed type and may form a complexwith the metal surface.